2014
DOI: 10.1016/j.jjcc.2013.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and determinants of elevated high-sensitivity cardiac troponin T in hypertrophic cardiomyopathy

Abstract: The results demonstrated that hs-cTnT was elevated in a significant number of our HCM patients; therefore, hs-cTnT can be introduced as a valuable marker of myocardial injury in HCM patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
26
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 27 publications
5
26
2
1
Order By: Relevance
“…Previous studies have also shown that cardiac troponins are significantly associated with LA dimensions in HC. 7,9,10,12 Combined with the positive correlations between serum cTnI and LV volume (LVEDVI and LVESVI) found in this study, which have also been indicated by Okamoto et al, 11 we speculate that serum cardiac troponins in HC may be partially related to increased LV-filling pressures.…”
Section: Discussionsupporting
confidence: 88%
“…Previous studies have also shown that cardiac troponins are significantly associated with LA dimensions in HC. 7,9,10,12 Combined with the positive correlations between serum cTnI and LV volume (LVEDVI and LVESVI) found in this study, which have also been indicated by Okamoto et al, 11 we speculate that serum cardiac troponins in HC may be partially related to increased LV-filling pressures.…”
Section: Discussionsupporting
confidence: 88%
“…37 Exercise can increase Tn levels. 38 Clinical correlates: troponin elevation in HCM is associated with greater LV wall thickness 37,[39][40][41][42][43] and LV mass. [44][45][46] Two studies found Tn elevation in patients with LV outflow tract obstruction 37,42 but another found no correlation.…”
Section: Familial Cardiomyopathy Tnnt2 Tnni3 Tnnc1mentioning
confidence: 99%
“…38 Clinical correlates: troponin elevation in HCM is associated with greater LV wall thickness 37,[39][40][41][42][43] and LV mass. [44][45][46] Two studies found Tn elevation in patients with LV outflow tract obstruction 37,42 but another found no correlation. 40 The natural history of HCM includes progression to heart failure and Tn elevation is present in those with LV systolic dysfunction 37,40,44 although the degree of hs-TnT elevation does not correlate linearly with ejection fraction.…”
Section: Familial Cardiomyopathy Tnnt2 Tnni3 Tnnc1mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, there are several noncoronary-related conditions, known to cause an increase in cTn, which should be considered in the differential diagnosis of patients presenting with troponin elevation (5)(6)(7)(8). Also, there are several factors which can influence the upper reference limits of hs-cTnT (97.5th and 99th…”
Section: Introductionmentioning
confidence: 99%